Brachypodium sylvaticum, a Model for Perennial Grasses: Transformation and Inbred Line Development - Steinwand, Michael A. (Public Library of Science, 2013)
Perennial species offer significant advantages as crops including reduced soil erosion, lower energy inputs after the first year, deeper root systems that access more soil moisture, and decreased fertilizer inputs due to the remobilization of nutrients at the end of the growing season. These advantages are particularly relevant for emerging biomass crops and it is projected that perennial grasses will be among the most important dedicated biomass crops. The advantages offered by perennial crops could also prove favorable for incorporation into annual grain crops like wheat, rice, sorghum and barley, especially under the dryer and more variable climate conditions projected for many grain-producing regions. Thus, it would be useful to have a perennial model system to test biotechnological approaches to crop improvement and for fundamental research. The perennial grass Brachypodium sylvaticum is a candidate for such a model because it is diploid, has a small genome, is self-fertile, has a modest stature, and short generation time. Its close relationship to the annual model Brachypodium distachyon will facilitate comparative studies and allow researchers to leverage the resources developed for B . distachyon . Here we report on the development of two keystone resources that are essential for a model plant: high-efficiency transformation and inbred lines. Using Agrobacterium tumefaciens-mediated transformation we achieved an average transformation efficiency of 67%. We also surveyed the genetic diversity of 19 accessions from the National Plant Germplasm System using SSR markers and created 15 inbred lines.